Solving Systems of Equations by Elimination Help

Hey, I understand the concept for this, but for some reason I can't seem to get the answers right. I don't know what I'm doing wrong. This is one of the problems I did and my work.

4x + 8y = 20

-4x + 2y = -30

4x + 8y/8 = 20/8

4x/4x + y = 2.5/4x

y = 2.5/4x

4x + 8(2.5/4x) = 20

4x/4 + 4.75 = 20/4

x + 4.75 -4.75 = 5 - 4.75

x = 0.25

4(.25) + 8y = 20

1 + 8y/8 = 20/8

1 -1 + y = 2.2 - 1

y = 1.2

**CHECK:**

4x + 8y = 20

4(.25) + 8(1.2) = 20

1 + 9.6 =/= 20

10.6 =/= 20

Thanks in advance! :)

Re: Solving Systems of Equations by Elimination Help

First of all, it appears you are trying to use the substitution method, which is the long way in this case considering the x values can be eliminated immediately by adding the two equations.

Anyway, your mistakes come from when you are dividing. In an equation, when you need to undo a multiplication using division, to do ANY division, it is ALWAYS done to EVERYTHING on both sides, not just to one term.

Re: Solving Systems of Equations by Elimination Help

Really? I did another problem where I only divided one on each side and the answer was right.

4x/4x + y = -3/4

Re: Solving Systems of Equations by Elimination Help

elimination method: add the terms ...

4x + 8y = 20

-4x + 2y = -30

---------------

... 10y = -10

y = -1

now use the solution for y either of the original equations to find x

Re: Solving Systems of Equations by Elimination Help

Then please tell us what that problem was!

Re: Solving Systems of Equations by Elimination Help

-4x - 2y = -12

4x + 8y/8 = -24/8

4x/4x + y = -3/4x

y = -3/4x

4x + 8(-3/4x) = -24

4x - 6 + b = -24 + b

4x/4 = 18/4

x = 4.5 (I noticed that I made a mistake or two, but when I checked it, everything was right so I just left it.)

4(4.5) + 8y = -24

18 -18 + 8y = -24 - 18

8y/8 = 42/8

y = 6

4(4.5) + 8(6) = -24

18 - 42 = -24

-24 = -24

-4(4.5) - 2(-6) = -12

-18 + 6 = -12

-12 = -12

x = 4.5

y = 6

Re: Solving Systems of Equations by Elimination Help

Quote:

Originally Posted by

**drakojan201** -4x - 2y = -12

4x + 8y/8 = -24/8

4x/4x + y = -3/4x

y = -3/4x

You seem unaware of the basics...better start listeming in math class

Start by getting the y-term by itself:

2y = -4x + 12

Divide by 2:

y = -2x + 6

That's it.